The Conduct of Refresher Course as a Tool for Continuing Professional Education Programme for College Librarians: The University of Mumbai Experiment - Rajhansa, Vijaya (Journal of Information and Knowledge, 2014)
The article indicates that although technically Refresher Course (RC) and Continuing Education Programmes (CPE) are different, their professional objectives are overlapping. More effectiveness could be rendered to Refresher Course, if it is conducted as a tool for CPE. The Refresher Course could be made a lively and fruitful exercise by implanting the inputs of CPE in the Refresher Course. This takes care of the appropriate course components of the Refresher Course and at the same time removes its monotony. The article illustrates how this line of thinking was experimented while designing the four need based Refresher Courses for College Librarians in the Department of Library & Information Science, University of Mumbai, during the period 1996 to 1999. The overall impact of the Refresher Course as reflected in session by session feedback, and the participants’ response to the questionnaires indicated their approval of the well-constructed and well-organised courses, which besides refreshing their knowledge were very informative for them. The participants also expressed the further need for providing guidance in hard core practical librarianship.